From raw-barbarian to Miss Beauty Queen: indigeneity, identity and the perception of beauty in Taiwan - Lin, Hsiao-Ching, author; Kim, Joon K., advisor; Doe, Sue, committee member; Swensen, Thomas Michael, committee member (Colorado State University. Libraries, 2017)
Using an auto-ethnographical method and sharing my own experience growing up in Taipei, Taiwan, this thesis discusses the association between Taiwanese indigeneity and the perception of beauty in contemporary Taiwan. For the purpose of this study, this thesis references the theory of beauty and indigenous studies to explore the affectability regarding the colonial history of Taiwan, body images, international influence, the eliminatory elements of colonial structures, and the modern pastiche of Taiwanese aesthetic. Furthermore, this thesis analyzes Chinese-settler colonial influence in Taiwan by discussing the media's impact and the artistic innovations in the biggest city, Taipei. Two major conclusions are drawn: first, Taiwanese indigeneity, infused in contemporary art, counteracts the forces of Chinese orthodoxy, international influence, and Taiwanese modern aesthetic. Second, Taiwanese indigenous characteristics often contain pastiche of Taiwanese aesthetics, a fixed beauty standard, which consists of various elements such as Chinese elegance/nostalgia, modern comfort/convenience, and the indigenous acceptance/sublimation.